Hydrogenolysis of n-Butane over Ru/AlO Catalysts - Janusz Ryczkowski; Marcin Kuśmierz; Dobiesław Nazimek; Sylwia Pasieczna (Adsorption Science & Technology)
Preliminary studies were undertaken of the preparation parameters of DIM (double impregnation method) influencing metal loading, ruthenium catalyst dispersion and n-butane hydrogenolysis. Ruthenium red was used as the metal precursor of Ru/Al 2 O 3 catalysts. The infrared spectra of ruthenium red and EDTA adsorbed on alumina indicated that interaction occurs between adsorbates and the support surface. An extension of the impregnation time by ruthenium red caused a slight shift of the asymmetric –COO − band that may be explained by interaction between ruthenium and adsorbed EDTA. The small change in the –COO − band position was due to the nature of the metal–EDTA bond formed. An increase in metal loading led to an increase in ruthenium dispersion. Measurements of the rate of hydrogenolysis of n-butane were carried out in a gradientless reactor. All kinetic experiments were conducted under conditions where the hydrogen/n-butane molar ratio was 9:1, and involved isothermal determination of the relationship between the n-butane reaction rate and the corresponding degree of conversion (iso-X). The absence of propane and the presence of isobutane (at lower temperature) among the products were discussed.